Relation of lead (pb) levels with ion calcium (ca2+) levels of alley gas station’s operators - Sakinah Nur Fadillah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Lead (Pb) impaired absorption of calcium ions (Ca2+). The purpose of this study was to measure Pb levels, Ca2+ levels and the relationship between Pb and Ca2 + levels. This study was an observational study with a cross-sectional approach. Data obtained from interviewa and questionnaires. Measurement of blood Pb using AAS and mesuarement of Ca2+ level using the photometer method. Samples were taken from 20 gas station operators. The result of this study was the average Pb levels and Ca2+ levels in the blood of SPBU operators were 7,50 and 8,34, and the higher the Pb levels resulting in lower Ca2+ levels